Tinjauan Yuridis Normatif Eksekusi Penghitungan Suara Ulang Pemilihan Kepala Desa Bode Lor Oleh PTUN Bandung - Firdausiyah, Salsabila; Hafizd, Jefik Zulfikar; Arfan, Am’mar Abdullah (PT. AORSA ADIVISI KAKA, 2026)
The State Administrative Court is one of the executors of judicial power for people seeking justice regarding State Administrative disputes. Settlement of disputes in the general election of village heads through a State Administrative Court lawsuit is the appropriate legal action because the PTUN has the authority to decide and adjudicate disputes at the election stages. This research aims to review the execution process of decision Number 57/G/2020/PTUN.BDG. The method used in this research is qualitative with a normative juridical approach. The data collection used is literature. The results of this research show that the decision letter in question has been decided to be valid and declared to remain in effect since the PTUN decision has permanent legal force and the Regent of Cirebon did not make a new decision because the person who received the most votes in the process of recounting the votes at the Court regarding the elected Kuwu did not change. even though there were additional votes for all candidates from votes that were previously considered invalid.